Tumor-Suppressive Role of microRNA-202-3p in Hepatocellular Carcinoma Through the KDM3A/HOXA1/MEIS3 Pathway - Zhang, Yijie; Pan, Qi; Shao, Zigong (Frontiers in Cell and Developmental Biology, 2021)
Hepatocellular carcinoma (HCC) represents a malignant tumor predominantly arising in the setting of cirrhosis and is the third most common cause of cancer-associated death on a global scale. The heterogeneous nature of HCC and limited well-recognized biomarkers may contribute to poor patient prognosis and treatment failure. In this study, we identified expression pattern of microRNA-202-3p (miR-202-3p) in HCC and characterized its functional role as well as related mechanisms. Firstly, we collected 50 HCC tissues and 38 normal liver tissues, and after bioinformatics prediction, the expression of miR-202-3p and KDM3A was determined in the tissues. We found lowly expressed miR-202-3p and overexpressed KDM3A in HCC tissues. Then, dual-luciferase reporter gene assay was employed to test the presence of miR-202-3p binding sites in the 3’UTR of KDM3A and chromatin immunoprecipitation assay to HOXA1 interaction with KDM3A and MEIS3. It has been confirmed that miR-202-3p negatively regulated KDM3A responsible for increasing the expression of HOXA1 by eliminating the H3K9me2 in HCC cells. HOXA1 could evidently increase H3K4me1 and H3K27ac enrichment in the MEIS3 enhancer region and enhance the expression of MEIS3. Functional assays were also performed with the results showing that upregulated miR-202-3p or downregulated KDM3A retarded HCC cell viability, migration and invasion. In addition, HepG2 cells were xenografted into nude mice, and we demonstrated that upregulated miR-202-3p reduced the growth of human HCC cells in vivo. Taken together, the present study elicits a novel miR-202-3p/KDM3A/HOXA1/MEIS3 pathway in HCC, potentiating an exquisite therapeutic target for HCC.